Implementasi Nilai-Nilai Aqidah Akhlaq Dalam Meningkatkan Kepedulian Sosial - Maftuchatur Rohmah; Layli Masruroh (Al-Misbah (Jurnal Islamic Studies), 2019)
One of the subjects taught at school is Aqidah Akhaq. This learning is done to instill good aqidah and morality to students. But with just learning it seems lacking without any implementation of the learning. The title of this research is "implementation of the values of aqidah akhlaq in increasing social awareness of case studies in class X MA al Qur'an La Raiba Hanifida" with a focus of research on the values of aqidah akhlaq students of MA al Quran La Raiba Hanifida and how it is implemented towards social care. The purpose of this research is to find out the implementation of Aqeedah Ahlaq towards social care case studies in class X MA al Quran La Raiba Hanifida. This research uses descriptive qualitative. Ways to collect data by interview, observation and documentation. While data collection techniques by reducing data and verifying data. Based on the results of research conducted that the values or attitudes of students of class X MA al Qur'an La Raiba Hanifida differ from one another. This is influenced by different family backgrounds, schools and environments. To equalize and increase the social awareness of students at the MA al Qur'an, La Raiba Hanifida collaborates with pesantren to hold several activities that are expected to be able to increase the social awareness of students. Among these activities include: teaching asthma pilgrims, teaching flash pupils and TPQ, training, engaging in all events, social and social services.